Pertumbuhan Laba Dan Struktur Modal Terhadap Kualitas Laba pada Perusahaan Pertambangan di Indonesia - Ayu Winarti; Aditya Amanda Pane; Sucitra Dewi (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to determine the effect of earnings growth and capital structure on earnings quality in mining companies listed on the Indonesia Stock Exchange for the period 2020-2022. The population of this study were 41 mining companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sampling method used in this study is purposive sampling method, so that the results obtained are 19 sample companies for 3 years of observation (2020-2022). The data collection method used in this study is to use the documentation method, which includes the process of collecting company data and taking information directly from the company's web and the Indonesia Stock Exchange web. The type of data used in this research is quantitative data. The data analysis method used is descriptive analysis, classical assumption test which is divided into 4 tests, namely normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. next is multiple linear analysis test and the last is hypothesis testing, hypothesis testing has 3 parts, namely partial test (t test), simultaneous test (F test) and determination coefficient test (R2). This test was conducted using the SPSS application. The results of this study indicate that earnings growth has a positive and significant effect on earnings quality and capital structure has a negative and significant effect on earnings quality. Simultaneously, the results show that earnings growth and capital structure together have a significant effect on earnings quality in mining companies listed on the Indonesia Stock Exchange for the period 2020-2022.